Using Mixed-methods Research in Health & Education in Nepal - Mahato, Preeti; Angell, Caterine; van Teijlingen, Edwin; Simkhada, Padam P (Journal of Health Promotion, 2018)
In the areas of health promotion and health education, mixed-methods research approach has become widely used. In mixed-methods research, also called multi-methods research, the researchers combine quantitative and qualitative research designs in a single study. This paper introduces the mixed-methods approach for use in research in health education. To illustrate this pragmatic research approach we are including an example of mixed-methods research as applied in Nepalese research. Journal of Health Promotion Vol.6 2008, p.45-48